(3MGTjI Ydi TQM GdYVOj deNJUQ GHf GdMGLHs - (3GdNhfSGQj, LeGd GdOjf Hf GdMSjf Hf LeGd GdOjf, J (B1125(3g`s
(3ChdgG (B:s
(3YfO ef LhR chf GddaX UGdMG ddLejY gPG eJYdb Hcd (B...s
(3BNQgG (B:s
(3GMJeGd GdYgO aj cd eSfO Hd jLQj Pdc aj GdYcS CjVG(B... (3hjchf Pdc GdESfGO bQjfI GdYgO aJOHQ gPGs
(3JHUQI GdYfhGf (B:s
(3aj eYLe GdeDdajf(B: (3MGTjI Ydi eNJUQ GdCUhds
(3JHUQI GdeDda (B:s
(3hjQhi aj SfI haGJg(B: 112(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B501s
Keywords: (3CUhd Gdabgs